Melanau and Malay kinship terminologies / Mohamad Musa Bohari - Bohari, Mohamad Musa
All societies have a classificatory system of determining kinship terminology. Our history, as human beings, lies on our lineage and ancestry through combinations of marriage and parentage ties. This research is a study of mankind’s history in term of kinship. The study analyzed the Melanau and Malay kinship terminologies from the semantics’ perspective of componential analysis. The study compared the kinship terms used in these languages by breaking down the lexemes into different components (semantic features) as to investigate the way they represent the meaning of those terminologies.